2017
DOI: 10.1590/s0004-2803.201700000-38
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mucin Phenotype Can Predict Gastric Cancer Recurrence After Endoscopic Mucosal Resection

Abstract: -Background -Endoscopic mucosal resection is still considered an accepted treatment for early gastric cancer for selected cases. Histopathologic criteria for curative endoscopic resection are intramucosal well-differentiated adenocarcinoma, lateral and deep margins free of tumor, no histological ulceration, and no venous or lymphatic embolism. A 5% local recurrence rate has been described even when all the above-mentioned criteria are met. On the other hand, antigen expression by tumoral cells has been related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
(45 reference statements)
2
11
0
1
Order By: Relevance
“…That is to say, the progression of gastric precancerous lesions to GC is a slow and gradual development process, at least targeted monitoring can be performed by mucin typing, and there is an opportunity to detect and remove tumorous lesions early. Although there are currently no clinically deterministic predictive biomarkers in clinical use, the use of mucin staining for subtype analysis can further stratify people who are already at risk (Hondo et al, 2017). In this study, we explored the changes of different mucus phenotypes during the progression of gastric disease.…”
Section: Discussionmentioning
confidence: 99%
“…That is to say, the progression of gastric precancerous lesions to GC is a slow and gradual development process, at least targeted monitoring can be performed by mucin typing, and there is an opportunity to detect and remove tumorous lesions early. Although there are currently no clinically deterministic predictive biomarkers in clinical use, the use of mucin staining for subtype analysis can further stratify people who are already at risk (Hondo et al, 2017). In this study, we explored the changes of different mucus phenotypes during the progression of gastric disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings from our group corroborate the present results 23 . It is possible that a refinement of the expanded criteria with mucin expression characterization may increase the accuracy of selecting the appropriate patients for ESD 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that patients are usually asymptomatic and that relapsed GC patients have poor prognosis, many doctors recognize the importance of surveillance in detecting recurrence[ 78 ]. Studies have shown that hematogenous metastasis is the most frequent recurrence pattern during the first year following resection[ 79 ], and identification of a simple method to monitor patients, for example, using serum lncRNAs, is a top priority.…”
Section: Lncrnas Dysregulated In Peripheral Blood and In Gastric Acidmentioning
confidence: 99%
“…These authors found that according to the 7 th edition of the TNM classification, classification of stage T4b and N0 as stage IIIA had statistical significance in regard to the survival outcome and in predicting prognoses in Chinese GC patients. Given that lymph node and distant metastasis were found to be key factors in the prognosis of GC patients, we identified the lncRNAs that correlated with lymph node, distant metastasis and the TNM stage, as shown in Table 1 [ 14 - 17 , 23 , 25 - 30 , 32 , 33 , 35 , 36 , 40 , 43 , 44 , 53 , 57 , 58 , 69 , 74 - 78 , 80 - 132 ].…”
Section: Lncrnas and Clinical Correlationmentioning
confidence: 99%